2020
DOI: 10.3126/njr.v9i2.27427
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Plantar Fasciitis and its Relation to Body Mass Index and Heel Pad Thickness

Abstract: Introduction: To study the sonographic appearance of plantar fascia in clinically suspected cases of plantar fasciitis (PFs) using both quantitative and qualitative parameters, and to establish the correlation between plantar fasciitis, body mass index (BMI) and heel pad thickness (HPT). Methods: In this case controlled analytical study, we sonographically evaluated 100 patients with clinical plantar fasciitis (unilateral: 90, bilateral: 10 with mean age 46.9yrs) and control group of 60 (120 heels) healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…Both were found statistically significant (p<0.001). The mean plantar fascia thickness in the affected leg was 5.07 ± 0.9 mm and the finding is consistent with that of Khatiwada et al (4.63 ± 0.55mm) [ 3 ]. The study by Karabay et al also found similar results, where the mean plantar fascia thickness in the affected leg was 4.79 mm but no significant difference was found between heel pads of the diseased and healthy feet [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Both were found statistically significant (p<0.001). The mean plantar fascia thickness in the affected leg was 5.07 ± 0.9 mm and the finding is consistent with that of Khatiwada et al (4.63 ± 0.55mm) [ 3 ]. The study by Karabay et al also found similar results, where the mean plantar fascia thickness in the affected leg was 4.79 mm but no significant difference was found between heel pads of the diseased and healthy feet [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study too, we found females were affected more than males. The mean age of occurrence of plantar fasciitis was found around 40 years which is similar to the study by Khatiwada et al where the mean age was 40 to 50 years and females were affected more [3]. The majority (73.3%) of the study participants had a sedentary lifestyle in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations